Analisis Strategi Pengembangan Usaha Warung Makan Mbah Sum (Studi Kasus Warung Makan Mbah Sum Saditan Brebes) - Riska Cita; Ari Kristiana; M.Syaifulloh (Global Leadership Organizational Research in Management, 2023)
Warung Makan Mbah Sum is a business operating in the culinary sector which was founded in 1990 and produces food and drinks. The aim of this research is to find out and analyze the business development strategy carried out by Warung Makan Mbah Sum to increase its income. Warung Makan Mbah Sum is located on Jl Husnitamrin RT 08/RW 04, Saditan Brebes. This research aims to analyze and implement the marketing mix at Warung Makan Mbah Sum. Marketing mix variables consist of product, price, promotion and distribution. The method used is a qualitative descriptive analysis approach. Data sources were obtained from observation, interviews and documentation. The object in preparing this research is business development strategies to increase income at the Mbah Sum Saditan Brebes Food Stall. The results of research in the field state that the business development strategy carried out by Warung Makan Mbah Sum is increasing product variants, maintaining low prices, improving service quality, and using new sales concepts. The obstacles faced by Warung Makan Mbah Sum in developing its business are lack of operational management, lack of facilities for eating on site, and pressure from outside (competitors). If seen from a strategy perspective, Warung Makan Mbah Sum has been able to develop its business to increase income.